AN ANALYSIS OF TENSE AND ASPECT IN THE “TANGLED” MOVIE SCRIPT - Herani, Isti Endila; Rachmijati, Cynantia (PROJECT (Professional Journal of English Education), 2019)
This study is an attempt to analyze the tense and aspects found inside the ”Tangled” movie script. The data source is a sentence or speech the verb contains tense and aspects found on “Tangled” movie script. The study applied descriptive qualitative method.This study belongs to a descriptive research because it collects and analyzes the data, after that draws a conclusion based on the data. Then this research belongs to qualitative research because it involves analyzing and explaining the data. Additionally, this research is designed in descriptive qualitative research because the research examines the types of the language used of Tense and Aspects in "Tangled" Movie Scripts. In this research the data source is “Tangled” Movie Script.In “Tangled” movie script, there was 61 sentences that researcher found in the uses of tense and aspect. From the result above the dominant types on tense and aspect in “Tangled” movie script was simple future and present perfect. In the “Tangled” movie script the researcher didn’t find tense and aspect in past perfect progressive, future progressive, future perfect and future perfect progressive.